ANALISIS KUANTITATIF KELENGKAPAN BERKAS REKAM MEDIS DI RUANGAN RAWA INAP KASUS BEDAH DI BLUD RSUD KOTA BAUBAU - Sinta, Niska Salsiani; Muzuh, Mega Ermasari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Quantitative analysis is a review of certain parts of the contents of medical records with the intention of finding specific deficiencies related to documentation (recording) in medical record files. Preliminary study results show that there are still incomplete forms. The purpose of this study was to determine the percentage of completeness of medical record files in the surgical case inpatient ward at the Baubau City Hospital BLUD 2018. This research used a descriptive research type and a quantitative approach with a total sample of 54 medical record files in the surgical case inpatient room. The results of the study showed that the results of the identification analysis in the entry and exit summary files in the surgical case inpatient ward of the 54 samples of the entry and exit summary files were most complete in the component name, gender, date of birth, each address was 100% and the most incomplete on the Age component of 3.70%. Identification analysis of medical resume files in the surgical case inpatient ward of 54 samples of medical resume files, the most complete in the medical record number component was 100% and the most incomplete in the address component was 100%. file identification analysisinformed concent in the surgical case inpatient room of 54 file samplesinformed concent the most complete in the name component was 46.29% and the most incomplete in the address component was 94.44%.